2021
DOI: 10.1053/j.jrn.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Area Is a Better Predictor Than Coronary Artery Calcification Score for Cardiovascular Outcomes and All-Cause Death in Patients on Hemodialysis

Abstract: Objectives: The aim of this study is to compare the prognostic effects of visceral fat area (VFA) with coronary artery calcification score (CACs) in patients on maintenance hemodialysis. Design and Methods: In the prospective study with no intervention, clinical characteristics and serum biochemical indexes at baseline for each patient were collected through the electronic medical records. Body composition assessment using bioelectrical impedance analysis, computed tomography examination with the Agatston scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…BMI as the traditional anthropometric parameter can only evaluate the total body fat, but not the fat distribution. In recent years, it has been discovered that central obesity with excessive accumulation of visceral fat significantly increases the risk of atherosclerosis, type 2 diabetes, cancer, and all-cause mortality ( Liu et al., 2019 ; Qiu et al., 2020 ; Xiong et al., 2021 ). This may be because the visceral fat is more active in storing dietary fatty acids, secreting adiponectin and inflammatory factors such as interleukin-6, tumor necrosis factor (TNF)-α, and colony-stimulating factor-1 ( Fontana et al., 2007 ; Harman-Boehm et al., 2007 ; Cartier et al., 2008 ; Kovacova et al., 2012 ; Wang et al., 2012 ; Huang et al., 2015 ; Tsujimoto and Kajio, 2017 ; Barberio et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMI as the traditional anthropometric parameter can only evaluate the total body fat, but not the fat distribution. In recent years, it has been discovered that central obesity with excessive accumulation of visceral fat significantly increases the risk of atherosclerosis, type 2 diabetes, cancer, and all-cause mortality ( Liu et al., 2019 ; Qiu et al., 2020 ; Xiong et al., 2021 ). This may be because the visceral fat is more active in storing dietary fatty acids, secreting adiponectin and inflammatory factors such as interleukin-6, tumor necrosis factor (TNF)-α, and colony-stimulating factor-1 ( Fontana et al., 2007 ; Harman-Boehm et al., 2007 ; Cartier et al., 2008 ; Kovacova et al., 2012 ; Wang et al., 2012 ; Huang et al., 2015 ; Tsujimoto and Kajio, 2017 ; Barberio et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 97 hemodialysis patients, Xiong et al found that visceral fat determined by BIA was associated with cardiovascular events (HR 9.21; 95% CI 1.49-56.76; visceral fat area ≥71.3 cm 2 vs. <71.3 cm 2 ; p = 0.017), cardiovascular mortality (HR 1.11; 95% CI 1.01-1.22; 1-cm 2 increase in fat mass area; p = 0.035), and all-cause mortality (HR 1.08; 95% CI 1.02-1.14; 1-cm 2 increase in fat mass area; p = 0.011) [110]. Okamoto et al followed 126 patients on maintenance hemodialysis for 60 months and reported multivariate Cox proportional hazards analysis results showing that a visceral fat area of >71.5 cm 2 , determined by CT, was an independent predictor of cardiovascular death (HR 4.46; 95% CI 1.24-16.05; p = 0.022) [111].…”
Section: Visceral Fat and Mortalitymentioning
confidence: 99%
“…Nutritional status and body composition were not related to the number of significantly lesioned coronary arteries in the presented study, this observation is in line with the fact that the symptoms of CAD do not correlate adequately with the extent of coronary lesions. The observations from other studies suggest the role of visceral fat accumulation as a good predictor for coronary calcification [ 34 ]. These differences might be caused by different methodologies, as in the present study only the number of significantly lesioned arteries was taken into count and total FM was assessed, while in the study by Xiong et al the structural advancement of CAD was assessed with tomography calcium score and segmental BIA was performed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observations from other studies suggest the role of visceral fat accumulation as a good predictor for coronary calcification [ 34 ]. These differences might be caused by different methodologies, as in the present study only the number of significantly lesioned arteries was taken into count and total FM was assessed, while in the study by Xiong et al the structural advancement of CAD was assessed with tomography calcium score and segmental BIA was performed [ 34 ]. However, the mentioned study group was also hemodialysis patients which could interfere BIA results [ 34 ].…”
Section: Discussionmentioning
confidence: 99%